Comparison of clinical profile between Plasmodium vivax and Plasmodium falciparum malaria in children in tertiary care hospital - Ravilala, Vinod Kumar; Ahmed, Shabbeer; Vanka, Murali Krishna; Seepana, Rajesh (International Journal of Contemporary Pediatrics, 2018)
Background: The high prevalence of uncomplicated malaria as seen in this study suggests the importance of timely diagnosis and effective treatment and encourages new activities to further decrease complicated malaria cases. Methods: In this study, malaria was diagnosed by conventional thick and thin peripheral smear stained with Leishman stain, examined under oil immersion. The slide was considered negative when there were no parasites in 100 HPF. Rapid diagnostic tests were based on detection of specific plasmodium antigen, LDH (optimal test) for Vivax and HRP2 for falciparum. The mode of presentations like fever, splenomegaly, vomiting, abdominal pain, laboratory investigations and complications were noted. Simple malaria was defined as Plasmodium vivax or Plasmodium falciparum malaria without any complications. All the statistical analysis was done by using SPSS 16 version and in MS Excel. Qualitative variables were expressed as frequencies and percentages. Chi-square was used for examining the categorical data. Results: A total 100 cases of malaria diagnosed by rapid diagnostic test and/or peripheral smear were studied. 69% of the cases were falciparum malaria and 31% of the cases were vivax malaria. Males were more commonly affected than females. Vivax malaria was most common between 5-10 years of age and falciparum malaria was more common in 0-5 years of age. Uncomplicated malaria was seen in 73% of the cases and complicated malaria was seen in 27% of the cases. Incidence of complicated malaria was more common in case of falciparum malaria. Fever, pallor, hepatomegaly and splenomegaly were significant for clinical diagnosis of malaria. Severe anaemia was the most common presentation of complicated malaria followed by jaundice. Cerebral malaria was more common in case of falciparum malaria. Metabolic acidosis and renal failure were more common in falciparum malaria. Hypoglycemia, significant bleeding and shock were more common in falciparum malaria. ARDS was most common in vivax malaria. Conclusions: This study emphasizes the importance of severity of P. Vivax malaria and recommends further studies to establish mortality and severity predictors specific to it.